2004
DOI: 10.1590/s0066-782x2004001700007
|View full text |Cite
|
Sign up to set email alerts
|

O polimorfismo A1166C do receptor tipo 1 da angiotensina II no infarto agudo do miocárdio

Abstract: ObjectiveTo assess the association of the A1166C polymorphism of the angiotensin II type-1 receptor (AT1R) gene with acute myocardial infarction and also with the severity of coronary artery disease. (OR = 1.35; AC vs AA (OR = 1.03; and AA+AC vs AA (OR = 1.33;. None of the severity criteria showed a significant correlation with the genotypes. Methods Conclusion According to our results, no correlation exists between the A1166C polymorphism of the angiotensin II type-1 receptor (AT1R) gene and acute myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The effects of Ang II are mediated by two distinct types of receptors: AT 1 and AT 2 , and the greatest interaction of this peptide occurs via the AT 1 receptors, causing vasoconstrictor action, arrhythmogenic effect, cell proliferation, thrombosis, coagulation, inflammation, and hypertrophy of vascular smooth muscle [ 114 , 115 ]. This Ang II signaling pathway with AT 1 receptors is carried out by the activation of the G protein, with consequent activation of phospholipase C- β and formation of 1,4,5-triphosphate and diacylglycerol, which in turn increases the intracellular concentration of calcium leading to vasoconstriction [ 116 ]. In addition to these effects, it is known that q Ang II via AT 1 receptors stimulates aldosterone secretion by the zona glomerulosa of the adrenal cortex [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of Ang II are mediated by two distinct types of receptors: AT 1 and AT 2 , and the greatest interaction of this peptide occurs via the AT 1 receptors, causing vasoconstrictor action, arrhythmogenic effect, cell proliferation, thrombosis, coagulation, inflammation, and hypertrophy of vascular smooth muscle [ 114 , 115 ]. This Ang II signaling pathway with AT 1 receptors is carried out by the activation of the G protein, with consequent activation of phospholipase C- β and formation of 1,4,5-triphosphate and diacylglycerol, which in turn increases the intracellular concentration of calcium leading to vasoconstriction [ 116 ]. In addition to these effects, it is known that q Ang II via AT 1 receptors stimulates aldosterone secretion by the zona glomerulosa of the adrenal cortex [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have suggested that genetic variants, including those of the genes for angiotensinogen (AGT) 1 , renin (REN) 2 , angiotensin-converting enzyme (ACE) 3 , angiotensin II receptor type 1 (AGTR1) 4,5 , and aldosterone synthase (CYP11B2) 6 increase the risk for EH. However, the influence of polymorphic forms of these genes has shown conflicting results in different populations 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Esse processo promove acoplamento com a proteína G que estimula a fosfolipase beta. Uma vez estimulada, ela induz a formação de trifosfato de inositol e DAG, liberando Ca 2+ citoplasmático ao passo que ativa PKC e adenil-ciclase (CONTRA et al, 2008;CARVALHO-FILHO et al, 2007;ARAÚJO et al, 2004). Após essa ligação, a angiotensina II estimula a musculatura vascular lisa através vias de sinalização, como a fosfolipase C, fosfolipase A2 e fosfolipase D. Além disso, participa da ação de inúmeras quinases, tais como tirosinaquinases, proteína quinase ativada por mitógenos (MAPKs).…”
Section: Revisão Da Literaturaunclassified
“…Após essa ligação, a angiotensina II estimula a musculatura vascular lisa através vias de sinalização, como a fosfolipase C, fosfolipase A2 e fosfolipase D. Além disso, participa da ação de inúmeras quinases, tais como tirosinaquinases, proteína quinase ativada por mitógenos (MAPKs). A Ang II também aciona a proteína ativadora-1, ativadores de transdução e transcrição (ESTEBAN, et al, 2008;ARAÚJO et al, 2004). Os mecanismos intracelulares da ANG II são mostrados na Figura 5 (CARVALHO-FILHO et al, 2008).…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation